Thinking Sociomaterially: Why Matter Matters in Medical Education. (June 2020) - MacLeod, Anna; Ajjawi, Rola
Abstract : Sociomaterial perspectives in research are those that encourage researchers to focus their inquiry on the relationships between people (social) and things (material), rather than focusing solely on people. The unique possibility of sociomaterial perspectives is increasingly recognized in health professions education scholarship. In an effort to support those who may be interested in engaging with the principles of sociomaterialism in their own work, the authors have developed a primer on this paradigm of research. This Invited Commentary—one of several exploring different philosophies of science—offers an overview of the ontological, epistemological, axiological, and methodological foundations of sociomateriality. The authors then put these ideas into action, highlighting the philosophical foundations of sociomaterial perspectives in a sample case study that tells the story of Lee, a resident involved in a medical error.